Effect of Leadership on Talent Management Process in Universities in Indonesia - Dyah Purwaningsih; Rasyid, Mohammad Kurniadi (Adpebi Science Series, 2022)
The aim of this research is to explore the effect of leadership on the talent management process in universities in Indonesia. This research used quantitative approach. The respondents were 108 talented education personnel from 12 universities in West-Java, Indonesia. The sampling method was used to collect data using surveys and questionnaires. The collected data from the respondents were analyzed using Structural Equation Model Partial Least Square (SEM-PLS). The Smart PLS 3.0 software was used to process the data. The study have found that leadership is proven to have an impact on the success of talent management. The results show that the application of leadership can support a better talent management process at universities.